Nanoelectronic Devices Based on Carbon Nanotubes - DMITRIEV, Victor Alexandrovich (Universidade Federal do Pará, 2017)
Carbon nanotubes are possible building blocks in the development of new generation of electronic devices. The carbon nanotubes allow one fabrication of devices using nanometric scales. They can be used in projects of a wide range of electronic and optoelectronic components such as diodes, transistors and interconnection elements, among others. This paper presents the state-of-the-art of this area, emphasizing the influence of quantum effects on the characteristics of such components.